Quasi-steady radiation of sound from turbulent sonic ergoregions - R Bürkle; A Gaidoukov; J R Anglin (New Journal of Physics, 2018)
Sonic Hawking radiation has recently been observed in dilute Bose–Einstein condensates (BECs), but it remains an open question whether this landmark achievement of atomic physics can lead to new insights into the effects on Hawking radiation of nonlinear back-reaction and new short-distance physics, as was originally hoped by Unruh when he introduced the sonic analogy. Furthermore, studies of sonic analog black holes have until now concentrated on (1+1)-dimensional scenarios, but Unruh’s sonic analogy for curved spacetime is only valid in more than one spatial dimension. We therefore model the evolution of a (2+1)-dimensional sonic black hole in a dilute BEC, over a long enough time to let the initial Corley–Jacobson instabilities saturate in vortex production and give way to a long-lived quasi-stationary state. In this quasi-equilibrium state we find the initial laminar ergoregion replaced by a turbulent zone that steadily radiates sound, but with a non-thermal power spectrum.